TRANSFORMATIONAL LEADERSHIP,WORK ENGAGEMENT AND EMPLOYEE CHAMPIONING BEHAVIOR: A THEORETICAL MODEL - Lubaba, Dinda Ayu; Udin, Udin (The journal of contemporary issues in business and government, 2021)
Purpose –This study aims to examine and analyze: (1) the direct effect of transformational leadership on employee championing behavior; (2) the direct influence of transformational leadership on work engagement; (3) the direct effect of work engagement on employee championing behavior; and (4) the effect of work engagement in mediating the relationship between transformational leadership and employee championing behavior. Methodology/Approach – This study uses a qualitative method by analyzing and reviewing the results of previous studies related to the relationship between transformational leadership, work engagement, and employee championing behavior. This study analyses the 20 most recent articles published in reputable international journals obtained by accessinghttps://www.emerald.com/, https://www.sciencedirect.com/, and https://scholar.google.com/. Findings – The results show that transformational leadership significantly affects employee championing behavior and work engagement. Furthermore, work engagement plays a vital role in mediating the relationship between transformational leadership and employee championing behavior. Originality/ Value/ Implication – Due to the finite and limited amount of existing research, the results of this study add value and develop literature related to the relationship between transformational leadership, work engagement, and employee championing behavior.